Territorial Competition: Theories, arguments, policies and lessons of the last 25 years - Nikolaos Kapitsinis; Theodore Metaxas (European Regional Science Association (ERSA), 2012)
Much of the current policy and scientific debate regarding territorial development focuses on territorial competition, which is a result of the outspread of competition (the centerpiece in classical and neoclassical political economy) over many aspects of other disciplines except economics, including geographical science. Territorial competition as a concept takes place among territorial units (states, regions or cities) in order to have the highest profits (mainly, economic) for the winner territorial unit. There are many scholars who have participated to the scientific discourse regarding territorial competition, some of them defending it and others dealing with it in a critical way. The basic difference and disagreement between these approaches is whether competition is a concept which is meaningful on both territorial and firm level or only on firm one and whether territories compete in the same way as firms do. These conflicting approaches differentiate in many issues including, among others, whether the determinant factors of firm performance are internal or both internal and external to the firm, whether the territory aims at development for its own sake or for competing to others and whether a territory can bankrupt like a firm. The debate over this issue is quite important since territorial policy over the last 20 years has focused on territorial competition. However, there are doubts regarding the extend to which this policy results in an equal way of territorial development, i.e. whether there is divergence or convergence. So, this situation, of the territorial competition existence in the centerpiece of territorial development policy, largely increases the significance of this study. This paper aims at studying the concept of territorial competition in depth by extensively reviewing the last 25 years of its development. In the first part this paper quotes the different approaches and their related arguments in an effort to investigate the theoretical context that the concept is introduced in the scientific and policy affairs. In the second part this study focuses on the way that territorial competition is applied on territorial development policy and its results in the territorial inequalities. In such a way it indicates the lessons that we could consider over this period, participating in the same time to the scientific dialogue regarding territorial competition.
Keywords: 330